Protein Profilesof Beef (Bos indicus), Pork (Sus domesticus),and SausagesBy Using SDS-PAGE (Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis) Method - Zilhadia, Zilhadia (Journal of Food and Pharmaceutical Sciences, 2014)
A research has been done to analyze the protein profile in fresh beef, fresh pork, and 10 beef sausage by using SDS PAGE (Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis) with 2 plate gel electrophoresis. From this research, we found several protein bands that become distinctive protein bands. On raw beef protein we found three bands that are not found in pork. They are protein band with molecular weight (MW) of 144,54 kDa, 81,28 kDa and 58,88 kDa respectively. On the raw pork, we found 5 protein bands that are not found in raw beef, namely protein bands with MW 154,88 kDa; 146,55 kDa; 83,18 kDa; 69,18 kDa and 61,66 kDa. There is a band on pork protein found on the second plate on MW gel is 69,18 kDa. Whereas in 10 samples of beef sausages we did not found any specific protein bands. This is presumably due to the difference in manufacturing process performed by the manufacturer.